MAIN TRENDS IN THE DEVELOPMENT OF LABOR LEGAL RELATIONS IN THE MODERN CONDITIONS: THE REGIME OF MARTIAL STATE IN UKRAINE - Dyban, Maksym; Sharko, Albina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to determine the prospects for the development and improvement of procedural legislation in the field of labor law after the termination or cancellation of the legal regime of martial law and to reveal the problem of legal regulation of labor relations during the legal regime of martial law. Research methods: during the research, general scientific and special legal methods of scientific knowledge were applied, in particular: system-structural method (allows you to explore the phenomenon in all the variety of connections, value systems, priorities), observation method (involves the collection of primary and further information about the object under study through purposeful, organized direct perception and direct recording of observed phenomena and processes), generalization method (the application of which establishes the general properties and characteristics of objects), methods of analysis and synthesis (certain logical operations that make it possible to study the phenomenon in general on the basis of combining interrelated elements into a single whole). Results: it is argued that the legal regulation of labor relations in the conditions of the legal regime of martial law has certain gaps, which requires additional research by the scientific community with the involvement of state bodies, lawyers and advocates. The article examines the main directions of development of the labor law of Ukraine, determined by the requirements of modernity. Discussion: the issue of the inefficiency of the regulation of labor relations during the period of martial law in Ukraine is raised, ways of solving problematic issues in this field of legal relations are proposed.